1989
DOI: 10.1111/j.1348-0421.1989.tb01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Proteins Derived from the Vegetative Cell Membrane in the Dormant Spore Coat of Bacillus subtilis

Abstract: To confirm the presence of the outer spore membrane in dormant spore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Despite the lack of conclusive morphological evidence for the presence of an outer spore membrane, there is functional and biochemical evidence to support the presence of such a structure in the mature spore. For instance, there is evidence that 11 spore coat proteins are related antigenically to membrane proteins from vegetative cells (Fujita et al. 1989; as cited in Henriques and Moran 2000).…”
Section: Outer Membranementioning
confidence: 99%
“…Despite the lack of conclusive morphological evidence for the presence of an outer spore membrane, there is functional and biochemical evidence to support the presence of such a structure in the mature spore. For instance, there is evidence that 11 spore coat proteins are related antigenically to membrane proteins from vegetative cells (Fujita et al. 1989; as cited in Henriques and Moran 2000).…”
Section: Outer Membranementioning
confidence: 99%
“…There is evidence for the outer forespore membrane remaining intact in spores of B. megaterium (67), and this issue must be resolved in B. subtilis. Fujita et al (32) demonstrated the presence of some vegetative cell membrane proteins in the coat, possibly indicating that at least some of the outer forespore membrane is still intact in the dormant spore.…”
Section: Spore Morphologymentioning
confidence: 99%
“…Alternatively, the inner coat itself may function as the permeability barrier and pretreatment with oxalic acid or phenol at a high temperature may cause partial destruction of the inner coat layer and enable the dyes to reach the outer pericortex region because spores treated with oxalic acid or phenol became susceptible to lysozyme ( Table 1). Failure of the dyes to penetrate the cortex suggests the existence of a secondary permeability barrier, that is, an outer membrane, which has been demonstrated biochemically in the spores of Bacillus megaterium (CraftsLighty & Ellar, 1980), by the morphological observation of variant spores lacking an exosporium (Koshikawa et al, 1984) and by showing the presence of vegetative cell membrane derived proteins in the spore coat of B. subtilis (Fujita et al, 1989). However, the localization and the integration of an outer membrane remain unclear with B. subtilis spores.…”
Section: Discussionmentioning
confidence: 99%